Reduced levels of threat and vulnerability to mental health and psychosocial support as consequences of climate disasters in Venezuela. - Suarez, Doris; Arana, Mayra; Suárez, Yumey (Conexiones UG, 2023)
Technological advances are continuously increasing and together with weather and geological phenomena trigger strong unexpected adverse events such as earthquakes, whose immediate actions are not effective due to, among other things. In this sense, the objective of this research was to analyze the decrease in the levels of threat and vulnerability of mental health and psychosocial support as consequences of climatic disasters in Venezuela, based on this principle and the realities that are experienced daily. in the provision of services, in addition to the fact that there are many communities that are unaware of what is related to the issue of risk management, leading to the fact that they are not clear about the way to act at the time of the succession of an event. The research paradigm selected according to the researcher’s position is Interpretive, the information collection was used, the transfer technique and the bibliographic review that allowed the design of the conclusions that were mainly focused on the risks accepted today by almost all of specialists refers to the combination of threats and vulnerability conditions. It is to a certain extent a conceptual construction to account for the relationships between society and nature that explain the occurrence of disasters, for this reason it was recommended to disseminate risk management programs to be established in the processes of institutional formation and to publicize their benefits to the communities, and once it is effective, present it to other institutions that will benefit from its foundations.